Differentiation of Human Induced Pluripotent Stem Cells into Brown and White Adipocytes: Role of Pax3. (23rd May 2014) - Mohsen-Kanson, Tala; Hafner, Anne-Laure; Wdziekonski, Brigitte; Takashima, Yasuhiro; Villageois, Phi; Carrière, Audrey; Svensson, Maria; Bagnis, Claude; Chignon-Sicard, Bérengère; Svensson, Per-Arne; Casteilla, Louis; Smith, Austin; et al.
Abstract: Identification of molecular mechanisms involved in generation of different types of adipocytes is progressing substantially in mice. However, much less is known regarding characterization of brown (BAP) and white adipocyte progenitors (WAPs) in humans, highlighting the need for an in vitro model of human adipocyte development. Here, we report a procedure to selectively derive BAP and WAPs from human-induced pluripotent stem cells. Molecular characterization of APs of both phenotypes revealed that BMP4, Hox8, Hoxc9, and HoxA5 genes were specifically expressed in WAPs, whereas expression of PRDM16, Dio2, and Pax3 marked BAPs. We focused on Pax3 and we showed that expression of this transcription factor was enriched in human perirenal white adipose tissue samples expressing UCP1 and in human classical brown fat. Finally, functional experiments indicated that Pax3 was a critical player of human AP fate as its ectopic expression led to convert WAPs into brown-like APs. Together, these data support a model in which Pax3 is a new marker of human BAPs and a molecular mediator of their fate. The findings of this study could lead to new anti-obesity therapies based on the recruitment of APs and constitute a platform for investigating in vitro the developmental origins of human white and brown adipocytes. Stem Cells   2014;32:1459–1467